Investigation of the environmental dependence of galaxy age in the CMASS galaxy sample of SDSS DR12 - Xin-Fa Deng (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In this study, I investigate the environmental dependence of galaxy age in the CMASS sample of the Sloan Digital Sky Survey Data Release 12 (SDSS DR12). It is found that galaxy age is very weakly correlated with the local environment. Considering the weak stellar mass-density relation of CMASS galaxies, it has been suggested that it is likely a combination of a strong age-stellar mass relation and a weak stellar mass-density relation. В работе исследована зависимость возраста галактик от окружающей среды в выборке CMASS из 12-го выпуска данных цифрового обзора неба Sloan (SDSS DR12). Установлено, что возраст галактик очень слабо коррелирует с локальной средой. Рассматривая слабую связь звездной массы и плотности галактик CMASS, предположено, что она, вероятно, является комбинацией сильной связи возраст-звездная масса и слабой связи звездная масса-плотность.
Keywords: Astrophysics